2012
DOI: 10.1167/12.10.11
|View full text |Cite
|
Sign up to set email alerts
|

Change in visual acuity is highly correlated with change in six image quality metrics independent of wavefront error and/or pupil diameter

Abstract: It is well known that the wavefront error (WFE) of the eye varies from individual to individual, with pupil diameter and with age. Numerous studies have been proposed evaluating the relationship between visual acuity and WFE but all these studies were performed with either a fixed pupil diameter or natural pupil diameter. It is still not clear if metrics of image quality correlates well with visual acuity independent of pupil diameter. Here we investigated the correlation between the change in visual acuity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 64 publications
3
61
0
Order By: Relevance
“…For this model, it was assumed (but not proven) that the lens would behave similarly on other highly aberrated eyes as the two eyes with keratoconus measured here. The visual image quality metric visual Strehl, which has previously been demonstrated to be well-correlated with change in acuity by Ravikumar et al 17,18 , was used to quantify the predicted change in visual acuity that would be experienced in the presence of these movements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this model, it was assumed (but not proven) that the lens would behave similarly on other highly aberrated eyes as the two eyes with keratoconus measured here. The visual image quality metric visual Strehl, which has previously been demonstrated to be well-correlated with change in acuity by Ravikumar et al 17,18 , was used to quantify the predicted change in visual acuity that would be experienced in the presence of these movements.…”
Section: Methodsmentioning
confidence: 99%
“…The choice to evaluate the impact in terms of visual image quality was based on evidence in the literature that root mean square (RMS) wavefront error is relatively poorly correlated with visual acuity 12 and that measured change in visual quality metrics (in particular visual Strehl ratio and neural sharpness) are highly correlated to a measured change in visual performance as measured by acuity in the presence of keratoconus (KC) aberrations. 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…To minimize the reflections from the trial lens, subjects were instructed to tip their heads slightly. 20 Head tilt with a cylindrical lens would induce unwanted off-axis aberrations; therefore, only subjects with little to no refractive cylinder were included. The anterior and posterior corneal radius, corneal aberrations, and corneal thickness of each eye were measured using the Bausch + Lomb Orbscan IIz corneal topographer (Rochester, NY).…”
Section: Clinical Study Design For Baseline Eye Modelsmentioning
confidence: 99%
“…26 A more recent study completed by Ravikumar et al found high correlation to distance visual acuity when taking the log of image quality metrics presented by Thibos et al; specifically logNS, logVSX, logVSMTF, and logPFSt gave R 2 Q0.86. 19,20,24 These previous studies show good correlation to distance visual acuity but still present a need for a through-focus image quality metric that takes into account the eye's natural aberrations, pupil diameter, and residual accommodative amplitude. The goal of this work was to develop a new image quality metric that is highly correlated with through-focus visual acuity and can be easily related to clinical measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation